2020
DOI: 10.1155/2020/4359305
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Coagulation Disorders and Inflammation by Hydrogen-Rich Solution Reduces Intestinal Ischemia/Reperfusion Injury in Rats through NF-κB/NLRP3 Pathway

Abstract: Intestinal ischemia/reperfusion (I/R) injury often causes inflammatory responses and coagulation disorders, which is further promoting the deterioration of the disease. Hydrogen has anti-inflammatory, antioxidative, and antiapoptotic properties against various diseases. However, the effect of hydrogen on coagulation dysfunction after intestinal I/R and the underlying mechanism remains unclear. The purpose of this study was to explore whether hydrogen-rich solution (HRS) could attenuate coagulation disorders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…However, excessive inflammation driven by the inflammasome and IL-1β signaling pathways promotes breast cancer, fibrosarcoma, gastric cancer, and lung metastasis in a context-dependent manner [ 48 ]. Some literature has shown that H 2 can be involved in various models of inflammation based on mechanisms of mitochondrial oxidation inhibition and NLRP3 inflammasome activation ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Effects Of H 2 On Inflammation and Itsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, excessive inflammation driven by the inflammasome and IL-1β signaling pathways promotes breast cancer, fibrosarcoma, gastric cancer, and lung metastasis in a context-dependent manner [ 48 ]. Some literature has shown that H 2 can be involved in various models of inflammation based on mechanisms of mitochondrial oxidation inhibition and NLRP3 inflammasome activation ( Table 1 ) [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ].…”
Section: Effects Of H 2 On Inflammation and Itsmentioning
confidence: 99%
“…H 2 exhibits anti-inflammatory, antioxidant, and anti-apoptotic effects, but its efficacy on intestinal I/R has been unclear. Yang et al investigated the effects of intravenous administration of H 2 -rich saline on intestinal I/R in an experiment on rats [ 17 ]. They reported that the administration of H 2 -rich saline improved the survival rate of the rats and ameliorated intestinal damage, edema, and apoptosis.…”
Section: Effects Of H 2 On Inflammation and Itsmentioning
confidence: 99%
See 2 more Smart Citations
“…Molecular hydrogen is currently recognized as an emerging therapeutic, as its supplemental application exerts protective effects in cardiovascular diseases [ 1 , 2 ], neurodegenerative diseases [ 3 ], inflammatory diseases [ 4 ], neuromuscular disorders [ 5 ], metabolic syndrome [ 6 ] diabetes [ 7 , 8 ], kidney disorders [ 9 , 10 ], and cancer [ 11 ]. The protective effects of molecular hydrogen are largely related to its antiapoptotic, anti-inflammatory, and antioxidative actions ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%